2020
DOI: 10.5539/jsd.v13n5p15
|View full text |Cite
|
Sign up to set email alerts
|

School Leadership for Sustainable Development: A Scoping Review

Abstract: Sustainable development within educational institutions encompasses an array of objectives as outlined in Agenda 21 (United Nations [UN], 1992). We recognize in this paper that there are cognate terminologies in the field of sustainable development: Education for Sustainable Development (ESD), Education for Sustainability (EfS), Development Education (DE), and Sustainability Education (SE). As stated in the Education for Sustainable Development toolkit (McKeown, 2002), ESD is the terminology most often employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
1
8
0
1
Order By: Relevance
“…Education for sustainable development requires school leaders to manage the resultant changes. The role of school leaders as change agents is to formulate policies and strategic plans in line with the goals of education for sustainable development (Mogaji & Newton, 2020). According to Chukwumah (2015) and Faiz et al (2019), strategic planning could be an effective management tool for policy direction, implementation strategies, action planning, monitoring, and evaluating results.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Education for sustainable development requires school leaders to manage the resultant changes. The role of school leaders as change agents is to formulate policies and strategic plans in line with the goals of education for sustainable development (Mogaji & Newton, 2020). According to Chukwumah (2015) and Faiz et al (2019), strategic planning could be an effective management tool for policy direction, implementation strategies, action planning, monitoring, and evaluating results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The success of reshaping education to address sustainable development goals depends greatly on the school leaders (Mogaji & Newton, 2020;Muller et al, 2020). The study conducted by Iqbal et al (2020) revealed the significance of effective leadership for sustainable development, as they could foster collaboration, motivation, and assistance for the transformational process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…η σχολική κουλτούρα και ο τρόπος αλληλεπίδρασης μεταξύ των εκπαιδευτικών (Kalaitzidis, 2012· Bucher, 2017· Mogren and Gericke, 2017· Nordén, 2018, 2. η δικτύωση των εκπαιδευτικών μεταξύ τους, είτε ως κοινότητες μάθησης, είτε ως περιβαλλοντικές ομάδες, 3. η δικτύωση μεταξύ σχολείων ή μεταξύ σχολείων και τοπικών οργανισμών που διευκολύνουν την ανταλλαγή γνώσεων, τη μεταβίβαση πληροφοριών και την υποστήριξη δράσεων (Bennell, 2015· Rauch, 2016· Li and Krasny, 2020· Mawela, 2020, 4. η σχολική ηγεσία, που θεωρείται κεντρικός κόμβος της διαδικασίας έναρξης και συνέχισης των προσπαθειών εφαρμογής περιβαλλοντικών δράσεων. Ειδικότερα, υπάρχει ένα πλήθος ερευνών για τη σχολική ηγεσία (Mogaji and Newton, 2020).…”
Section: εισαγωγήunclassified
“…Very little empirical research exists on the topic and literature on the role of educational leaders in ESD implementation is scant. As recently as 2013, Veronese and Kensler [25] high-lighted the dearth of information available on school leaders' efforts towards green schools in the U.S. Mogaji and Newton [26] found that almost all ESD research in the U.S. has been conducted since 2015 and that there still exists limited knowledge concerning the role of a school principal in initiating ESD. Complicating the issue is that approaches and assessment methods for research in ESD are vast and still in an early stage of development [23].…”
Section: Esd In Usamentioning
confidence: 99%
“…School effectiveness research, in particular, has produced a large amount of empirical evidence that underscores the significance of school management for the quality and performance of a school (cf., for example, [48,49]. The actions of the school management have an important effect on the teaching and school climate and on the self-image and motivation of teachers, and thus have an influence on the quality of teaching, education, or upbringing and thus ultimately also on the learning performance of the pupils [26,50].…”
Section: Sustainability and Esd As Leadership Responsibilitiesmentioning
confidence: 99%